2021
DOI: 10.1007/s00508-021-01839-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 lockdown on suicide attempts

Abstract: Summary Background In response to the current coronavirus disease 2019 (COVID-19) pandemic the Austrian government issued a lockdown from 16 March to 15 May 2020. As periods of economic and emotional burden have proven to detrimentally affect people’s psychological health, healthcare officials warned that the strict measures could have a serious impact on psychological health, leading to an increase in suicide attempts. Thus, the objective was to provide evidence for this assumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…(2020) revealed that younger adults, racial/ethnic minorities, essential workers, and unpaid adult caregivers reported having experienced elevated suicidal ideation associated with COVID-19. During lockdown in Austria, Carlin and colleagues (2021) showd an increase in attempted suicides during the lockdown period. Given the above, E-health interventions such as the Brief Adjustment Disorder Intervention (BADI) for the treatment of ICD-11 adjustment disorder ( Eimontas et al., 2018 ), and Skills for Life Adjustment and Resilience (SOLAR) ( O'Donnell et al., 2019 ), might lessen the incidence of AjD following lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) revealed that younger adults, racial/ethnic minorities, essential workers, and unpaid adult caregivers reported having experienced elevated suicidal ideation associated with COVID-19. During lockdown in Austria, Carlin and colleagues (2021) showd an increase in attempted suicides during the lockdown period. Given the above, E-health interventions such as the Brief Adjustment Disorder Intervention (BADI) for the treatment of ICD-11 adjustment disorder ( Eimontas et al., 2018 ), and Skills for Life Adjustment and Resilience (SOLAR) ( O'Donnell et al., 2019 ), might lessen the incidence of AjD following lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during the current data collection period, human movement restrictions with varied severity were already in place in several countries to curb the spread of COVID-19 [ 51 , 52 ]. Individuals may experience psychological fatigue and depressive and suicidal thoughts as a result of the lockdowns [ 53 , 54 ]. This may explain the more salient themes identified in present research that gravitate towards COVID-19 public health measures, biopsychosocial impact of the COVID-19 pandemic, and mental health support for at-risk individuals (i.e., Themes 1, 2, and 4, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Canadian epidemiologists projected 2,114 excess suicides in 2020-2021 related to unemployment due to COVID-19 (McIntyre & Lee, 2020). In an emergency room in Austria, the rates of suicide-related admissions tripled between 2019 and 2020 during COVID-19, and attributed to lockdowns (Carlin et al, 2021). These data highlight the need for depression assessment as well as an evaluation of risk for suicide.…”
Section: Mental Healthmentioning
confidence: 90%